PENGARUH PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA PT. ANGSANA JAYA - Lili Andriani, Bori Damayanto, (Universitas Batanghari Jambi, 2018)
Abstract This study aims to determine the description of respondents and the influence of personal selling on the decision to purchase products at PT. Angsana Jaya. Based on data analysis on the results of research that there is a significant influence between personal selling on the decision to purchase products at PT. Angsana Jaya. The results showed that personal selling of Suzuki brand motorcycles at PT. Angsana Jaya with 84.86% indicator approach, percentage of 88.81%, handling objections of 85.24%, closing sales of 88.57%, then the quality of service is quite good. Suzuki motorcycle purchase decision at PT. Angsana Jaya with 86.10% product offering indicator, 81.43% product quality, 86.19% product excellence, 78.00% interest, then purchase decision of Suzuki brand motorcycle at PT. Angsana Jaya is good. Based on the results of this t test shows that personal selling (X) has a positive and significant influence on the purchase decision of Suzuki brand motorcycles at PT. Angsana Jaya.Keyword : Personal Selling, Purchase Decision.